2006
DOI: 10.1111/j.1346-8138.2006.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of crusted scabies with a bullous pemphigoid‐like eruption and nail involvement

Abstract: We report a case of a 71-year-old man infected at a nursing home who developed a bullous pemphigoid-like eruption with nail involvement. He was diagnosed by his family doctor as suffering from eczema and was treated with topical corticosteroids, then blisters started appearing. He was next diagnosed as suffering from bullous pemphigoid and treated with oral prednisolone, which worsened his condition. He was finally diagnosed as having crusted scabies with bullous pemphigoid-like eruptions and nail involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…[5][6][7][8] Thus, our case is the first to be acknowledged as attributable to severe phimosis. It is likely that the constricting phimotic ring may have been responsible for significant lymph stasis and the subsequent dilatation of the superficial lymphatic channels.…”
Section: (C3) At the Dermo-epidermal Junctionmentioning
confidence: 65%
See 2 more Smart Citations
“…[5][6][7][8] Thus, our case is the first to be acknowledged as attributable to severe phimosis. It is likely that the constricting phimotic ring may have been responsible for significant lymph stasis and the subsequent dilatation of the superficial lymphatic channels.…”
Section: (C3) At the Dermo-epidermal Junctionmentioning
confidence: 65%
“…In the literature, linear immune deposits were found in eight of 31 cases of bullous scabies. [3][4][5][6][7][8][9][10] Bullous scabies can resemble autoimmune bullous diseases clinically, by light microscopy, and immunopathologically. 1 Several cases of bullous scabies have been reported as initially misdiagnosed and treated as bullous pemphigoid.…”
Section: Editormentioning
confidence: 99%
See 1 more Smart Citation
“…In such patients, an indirect immunofluorescent study is important to distinguish between scabies with blister formation and true bullous pemphigoid. [16] COMPLICATIONS COMPLICATIONS Crusted scabies is complicated by secondary bacterial infection by Staphylococcus aureus. They include impetigo, ecthyma, cellulitis and lymphangitis.…”
Section: Clinical Features Clinical Featuresmentioning
confidence: 99%
“…In cases of nail scabies, mites are found below and/or above the nail plates. Although the efficacy of ivermectin against nail scabies has not been evaluated in preclinical studies, its ineffectiveness against nail scabies has been clinically reported 69,76 . Particularly in cases where mites are found above the nail plate, the drug is unlikely to reach the pathogen.…”
Section: Treatment Of Scabiesmentioning
confidence: 99%